Development of SARS-CoV-2 Inhibitors Using Molecular Docking Study with Different Coronavirus Spike Protein and ACE2 - Israa Mohamed Shamkh; Dina Pratiwi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The novel coronavirus SARS-CoV-2 is an acute respiratory tract infection that emerged in Wuhan city, China. The spike protein of coronaviruses is the main driving force for host cell recognition and is responsible for binding to the ACE2 receptor on the host cell and mediates the fusion of host and viral membranes. Recognizing compounds that could form a complex with the spike protein (S-protein) potently could inhibit SARS-CoV-2 infections. The software was used to survey 300 plant natural compounds or derivatives for their binding ability with the SARS-CoV-2 S-protein. The docking score for ligands towards each protein was calculated to estimate the binding free energy. Four compounds showed a strong ability to bind with the S-protein (neohesperidin, quercetin 3-O-rutinoside-7-O-glucoside, 14-ketostypodiol diacetate, and hydroxypropyl methylcellulose) and used to predict its docking model and binding regions. The highest predicted ligand/protein affinity was with quercetin 3-O-rutinoside-7-O-glucoside followed by neohesperidin. The four compounds were also tested against other related coronavirus and showed their binding ability to S-protein of the bat, SARS, and MERS coronavirus strains, indicating that they could bind and block the spike activities and subsequently prevent them infection of different coronaviruses. Molecular docking also showed the probability of the four ligands binding to the host cell receptor ACE2. The interaction residues and the binding energy for the complexes were identified. The strong binding ability of the four compounds to the S-protein and the ACE2 protein indicates that they might be used to develop therapeutics specific against SARS-CoV-2 and close related human coronaviruses.